2011
DOI: 10.1016/j.ccr.2011.08.016
|View full text |Cite
|
Sign up to set email alerts
|

FoxM1 Promotes β-Catenin Nuclear Localization and Controls Wnt Target-Gene Expression and Glioma Tumorigenesis

Abstract: SUMMARY Wnt/β-catenin signaling is essential for stem cell regulation and tumorigenesis, but its molecular mechanisms are not fully understood. Here, we report that FoxM1 is a downstream component of Wnt signaling and is critical for β-catenin transcriptional function in tumor cells. Wnt3a increases the level and nuclear translocation of FoxM1, which binds directly to β-catenin and enhances β-catenin nuclear localization and transcriptional activity. Genetic deletion of FoxM1 in immortalized neural stem cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
580
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(613 citation statements)
references
References 26 publications
(51 reference statements)
27
580
5
1
Order By: Relevance
“…20 Furthermore, Wnt/b-catenin signaling is regulated by PLAGL2 and FoxM1 proto-oncogenes during gliomagenesis. 18,22 Here, we identified PY142 b-catenin as a nuclear b-catenin form that signals through transcriptional regulation in GBM. PY142 b-catenin is different from classical active b-catenin: PY142 b-catenin accumulates in the nucleus already in astrocytoma (grade II and III) samples and correlates with high levels of the migration marker Snail/Slug in tumor biopsies.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…20 Furthermore, Wnt/b-catenin signaling is regulated by PLAGL2 and FoxM1 proto-oncogenes during gliomagenesis. 18,22 Here, we identified PY142 b-catenin as a nuclear b-catenin form that signals through transcriptional regulation in GBM. PY142 b-catenin is different from classical active b-catenin: PY142 b-catenin accumulates in the nucleus already in astrocytoma (grade II and III) samples and correlates with high levels of the migration marker Snail/Slug in tumor biopsies.…”
Section: Resultsmentioning
confidence: 98%
“…[19][20][21] Overexpression of the Forkhead box M1 (FoxM1) transcription factor represents a critical mechanism further contributing to b-catenin signaling in GBM. 22 FoxM1 promotes b-catenin nuclear accumulation and together they form a complex with TCF4 required for glioma stem cell self-renewal and gliomagenesis. 22,23 Crosstalk between EGFR, c-Met and Wnt/b-catenin is well documented in cancer cells, thereby linking b-catenin signaling and cell migration induced by growth factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of this complex could, therefore, be the cause of Wnt inhibition in Wnt-dependent cancer cells leading to enhanced susceptibility for apoptosis and growth arrest. In accordance, Zhang et al showed that FOXM1 mutation or nuclear import prevented β-catenin nuclear accumulation in tumor cells, which led to a decrease in Wnt activity (134). Nevertheless, these findings do not explain how exactly β-catenin accumulates at the membrane.…”
Section: Targeting the Nk1r Compromises Canonical Wnt Signaling In Hementioning
confidence: 92%
“…In terms of glioblastoma, inactivated ALKBH5 inhibited the proliferation and tumorigenesis of GSCs and impaired GSCs self‐renewal 75. It is widely accepted that FOXM1 plays a pivotal role in regulating GSCs proliferation and self‐renewal 76, 77. ALKBH5 was found to demethylate FOXM1 nascent transcripts and promote FOXM1 expression, whereas long non‐coding RNA antisense of FOXM1 further promoted the interaction of FOXM1 nascent transcripts with ALKBH5.…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 99%